ECOLOGICAL AND ECONOMIC ASPECTS OF PLANNING OF URBAN DEVELOPMENT - Pozdnyakov, Andrey Leonidovich (Journal of Applied Engineering Science, 2017)
The article analyzes the foreign and Russian experience of urban development, taking into account the environmental and economic requirements for modern projects. Among the environmental priorities of many countries, the problems of organization of urban territory, development and maintenance of green spaces are brought to the forefront. The main problems, characteristic of large urban agglomerations, are combined in the following groups: transport, waste, energy, water, land use and landscapes.